Being-in-session : an interpretive phenomenological exploration of psychologists' experiences of practising psychotherapy in South Africa - Martin, Jarred H. (University of Pretoria, 2021)
Mini Dissertation (MA Clinical Psychology)--University of Pretoria, 2020.